AN UNSTEADY UNIT LOAD OF ROOF DEPOSIT - NIHEI, Yasuo; YOSHIDA, Takushi (PROCEEDINGS OF HYDRAULIC ENGINEERING, 2008)
A unit effluent load has been widely used for evaluation of pollutant loads flowing into eutrophic lakes and inner bays, although the applicability of the unit effluent load for non-point sources has been severely limited. This study presents newly an unsteady unit effluent load for roof-deposit load, one of non-point sources in urban area, using its association with dry fallout. For this purpose, we have conducted a long-term, continuous monitoring of the amount of sediments and nutrients on the roof (SSroof, TNroof and TProof) during two years. The measured results indicate the good correlations not only between SSroof and dry fallout, but also between SSroof and TNroof (TProof) . The unsteady effluent load is described with these relations and measured SPM. This method was applied to evaluate the temporal variations of roof-deposit loads, showing the fundamental validity of the present method.